Keterkaitan dan Interaksi Spasial Pertumbuhan Ekonomi di Pulau Jawa Tahun 2016-2019 - Kahlanaila Pahlifi; Zulfa Emalia; Ukhti Ciptawaty; I Wayan Suparta (Departement of Mathematics Education, 2024)
This research aims to analyze the spatial linkages between provinces on Java Island and analyze spatial interactions between provinces on Java Island. The metods and analytical tools used in this research are the Moran Index and Gravity Index. The variable used to analyze spatial linkages is the ADHK GRDP growth rate, while to analyze spatial interactions is the distance to cities and population. The results of the research show that there is no spatial linkage but empirically there is a spatial linkage, and the highest interaction values are in the City of Serang and the City of Jakarta, while the lowest interaction values are in the City of Serang and the City of Surabaya